Remediation of pesticides by microalgae as feasible approach in agriculture: bibliometric strategies - Verasoundarapandian, Gayathiri; Lim, Zheng Syuen; Mohamed Radziff, Syahirah Batrisyia; Taufik, Siti Hajar; Puasa, Nurul Aini; Shaharuddin, Noor Azmi; Merican, Faradina; Wong, Chiew-Yen; Lalung, Japareng; Ahmad, Siti Aqlima (MDPI, 2022)
Pesticide treatment dramatically reduces crop loss and enhances agricultural productivity, promoting global food security and economic growth. However, owing to high accrual and persistent tendency, pesticides could create significant ecological consequences when used often. Lately, the perspective has transitioned to implementing biological material, environmentally sustainable, and economical strategies via bioremediation approaches to eradicate pesticides contaminations. Microalgae were regarded as a prominent option for the detoxification of such hazardous contaminants. Sustainable application and remediation strategies of pesticides pollutants in the agriculture system by microalgae from the past studies, and recent advancements were integrated into this review. Bibliometric strategies to enhance the research advancements in pesticide bioremediation by microalgae between 2010 and 2020 were implemented through critical comparative analysis of documents from Scopus and PubMed databases. As a result, this study identified a growing annual research trend from 1994 to 2020 (nScopus > nPubMed). Global production of pesticide remediation by microalgae demonstrated significant contributions from India (23.8%) and China (16.7%). The author’s keyword clustering was visualized using bibliometric software (VOSviewer), which revealed the strongest network formed by “microalgae”, “bioremediation”, “biodegradation”, “cyanobacteria”, “wastewater”, and “pesticide” as significant to the research topic. Hence, this bibliometric review will facilitate the future roadmap for many scholars and authors who were drawing attention to the burgeoning research on bioremediation of pesticides to counteract environmental impacts while maintaining food sustainability.